Kegiatan Komunikasi Musisi Indie dalam Melakukan Tur Eropa - Mardhika Bagaskara Darmawan; Riza Hernawati (UNISBA Press, 2022)
Abstract. In the midst of the development of very sophisticated music and everything is only about business profits, there is a culture or genre that is often called indie where the people who work in it have different tastes from most people. Joe Million is an Indonesian indie musician who represents rap or hip-hop music with his own characteristics, at the end of 2019 Joe Million toured several cities in Europe with Indra Menus. This study focuses on